Análise da deglutição de neonatos e lactentes: impacto da forma de oferta e viscosidade do estímulo no diagnóstico videofluoroscópico - Hernandez, Ana Maria (2020)
Videofluoroscopy swallow studies are considered the gold standard for the dysphagia diagnosis. For greater confidence in the result, it is necessary to know the performance of the infant replicating the normal function situation, whether in terms of the form of offer, the mother's breast, as well as in the preparation of the of the liquid to be offered. To achieve this purpose, the research was divided into three studies. Study I – Analiyses of neonates and infants in breast-feeding and bottle feeding, aimed at assess the similarities and differences on infant swallowing dynamics secondary to the stimulus offered and the possible impacts on the videofluoroscopy swallowing study findings. A retrospective study of twenty five videofluoroscopy swallowing study was carried out in the two types of offer – breast and bottle. The results showed a statistically significant association between the two types of offer specially related to velar function. The study II – Rheological analyses of liquids offered in videofluoroscopy swallow study of neonates and infants, aimed at analysing the rheological properties of liquids usually presented during videofluosocopy swallow studies in Brazil. The greater similarity in the rheological properties of the fluids offered to those of the infant’s typical diet, greater precision in the diagnosis and safe diet prescription obtained. The findings of the study II allowed not only the rheological characterization of the samples, but deeper understanding of how their viscosities behave in deformation rates consistent with the conditions provided in the act of deglutition. Rheological evaluation is effective in obtaining quantitative data on the properties of liquids. However it constitutes a high-cost technique that depends on expensive equipment and its not available to the broader clinical population and health professionals. Hence, an attempt was made to research and compare a proposal for a simple and affordable evaluation of the viscosity of liquids.The Study III – Analysis of the flow of isolated liquids and in addition of barium sulfate according to the model proposed by International Dysphagia Diet Standardization Iniciative, aimed at analyse the fluidity of the same products evaluated in study II, using the model proposed by the International Dysphagia Diet Standartization Iniciative. The results of two sudies were compared and indicated that liquids with viscosity differences from 2 to 4 mL in the International Dysphagia Diet Standardization Iniciative, are classified in the same category l. Similar findings were obtained in the rheological study where, despite the 18 to eighteen and a half folds in liquid viscosity, the classificacion remains in the same category.The current research supports the idea and allowed to conclude that greater reliability wil be obtained in the diagnosis of the swallowing dynamics of neonates and infants in breast-feeding by replicating, as close as possible, the usual conditions of offer, considering the familiar form – breast-feeding, utensils of suply, as well, taking care on preparation and control of the liquids viscosity. This is particulary crucial in the pediatric evaluation to facilitate optimal participation and confidence on the results. In conclusion, it will contribute to the best professional practices in the clinic for dysphagic patients or those at risk for dysphagia, being able to indicate the best and safier diet for the patient, facilitating the control in the handling of the offer by their caregivers. This should avoid the risk of inaccurate diagnosis of deglutition function, that may result in unnecessary intervention like an early weaning or risk for pulmonary health